Widow Psychological Well-Being During Covid-19 Pandemic At Nagari Tandikat, Patamuan, Padang Pariaman Regency - Ilmiyanti Refi Fadila; Wanda Fitri; Jemkhairil Jemkhairil; Siska Novra Elvina (State Institute of Islamic Studies Batusangkar, 2022)
The emergence of COVID-19 has brought many changes in society. Therefore, this research focuses on discussing the psychological well-being of widows during the COVID-19 period in Nagari Tandikat, Patamuan districts, Padang Pariaman regency. The theoretical perspective uses Ryff's theory of psychological well-being consisted six basic dimensions. It uses a qualitative method with descriptive analysis. Observation and interviews were conducted in collecting data. The sampling technique used were purposive sampling for six widows as the informants. The result showed that most widows have a good psychological well-being in Nagari Tandikat. The informants meet all dimensions of psychological well-being such as have good self-acceptance, make their own living, are able to utilize human resources and natural resources, have directed life goals, and make the past as a lesson. However, there is one informant who has less positive relationship with another person.